Tinjauan Kelengkapan Pengisian Surat Rujukan Fktp Pada Pasien Gigi Di Rumah Sakit Umum Universitas Muhammadiyah Cirebon - Riantina Luxiarti; Alissa Olivia Juhana; Hendri Rosmawan (Awatara Publisher, 2024)
A referral system is mandatory for patients who are participants of social health insurance and health service providers. The purpose of this study was to find out the completeness of filling out the FLHF referral letter for dental patients when carrying out outpatient treatment at Muhammadiyah University General Hospital in Cirebon. This type of research used was descriptive method. The population used in this study were all FLHF referral letters for dental polyclinic patients in 2022 at Muhammadiyah University General Hospital in Cirebon, with a sample of 68 FLHF referral letters for dental patients.:The results of research conducted at this hospital, it can be concluded as follows that FLHF referral letters for dental patients were not 100% complete, out of 68 FKTP referral letters for dental patients, 78% dental patient referral letters were for complete category and 22% of dental patient referral letters in the incomplete category. Researcher suggest that hospitals should be able to provide education on the completeness of FLHF referral letters to Dental patients. Because this education can be used as a reference for applying referrals to optimize outpatient registration of Social Health Security Administrator for Dental Polyclinics patients